ANALISIS GAYA BAHASA PADA CERPEN “PERMINTAAN TERAKHIR” KARYA USMAR ISMAIL - Ignatius Dimas Adi Suarjaya; Dewi, Novita (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Language is one of the important aspects that need to be researched. The language that a person uses can be conveyed orally or in writing. One of the forms of language used in writing can be found in the form of literary works. Literary works are often used as tools or media to be studied in more depth related to the structure and content in the literary work. The purpose of this study was to determine the linguistic characteristics used by Oesmar Ismail in his short story entitled "Permintaan Terakhir". The problem focuses on the style of language and also the language used in the short story "Permintaan Terakhir" by Oesmar Ismail. Qualitative descriptive methods were used in this study. Data collection techniques consist of reading, recording and analyzing. In examining the short story "Permintaan Terakhir" the researcher obtained a language style of repetition of three quotations, litotes of three quotations, symbolic of one quotation, hyperbole of four quotations, metaphor of one quotation, simile of two quotations, and climax of four quotations.